Graph the line for this problem: y=3x+6

\( y=3x+6\\\\for\ x=0\to y=3\cdot0+6=6\to A(0;\ 6)\\\\for\ x=-2\to y=3\cdot(-2)+6=-6+6=0\to B(-2;\ 0) \)

\( y=3x+6 \\ \\x=0 \\ \\y=3*0+6\\ \\y=6 \\ \\A(0,6) \)


\( y=0 \\ \\0=3x+6\\ \\3x=-6/:3\\ \\x=-2 \\ \\B(-2,0) \)


\( y=3x+6\\\\for\ x=0\to y=3\cdot0+6=6\to A(0;\ 6)\\\\for\ x=-2\to y=3\cdot(-2)+6=-6+6=0\to B(-2;\ 0) \) \( y=3x+6 \\ \\x=0 \\ \\y=3*0+6\\ \\y=6 \\ \\A(0,6) \)
\( y=3x+6\\\\for\ x=0\to y=3\cdot0+6=6\to A(0;\ 6)\\\\for\ x=-2\to y=3\cdot(-2)+6=-6+6=0\to B(-2;\ 0) \) \( y=3x+6 \\ \\x=0 \\ \\y=3*0+6\\ \\y=6 \\ \\A(0,6) \)

RELATED: